ADHD, ODD, and CD: Do They Belong to a Common Psychopathological Spectrum? A Case Series. (11th October 2012) - Ghosh, Sayanti; Sinha, Mausumi
Abstract : Purpose of Research . Numerous studies have reported comorbidities, overlapping symptoms, and shared risk factors among cases of attention deficit hyperactivity disorder (ADHD), oppositional defiant disorder (ODD) and conduct disorder (CD). We present three adolescent males aged 13–16 years with conduct disorder having past history of ADHD and ODD. Principal Result . The symptom profile especially in domains of aggression, hostility, and emotionality as well as the manner of progression from ADHD to ODD and CD in the above cases shows a similar pattern. Conclusion . These common developmental pathways and overlapping symptoms suggest the possibility of a common psychopathological spectrum encompassing the three externalizing disorders.